2013
DOI: 10.7554/elife.00036
|View full text |Cite
|
Sign up to set email alerts
|

Mammalian genes induce partially reprogrammed pluripotent stem cells in non-mammalian vertebrate and invertebrate species

Abstract: Cells are fundamental units of life, but little is known about evolution of cell states. Induced pluripotent stem cells (iPSCs) are once differentiated cells that have been re-programmed to an embryonic stem cell-like state, providing a powerful platform for biology and medicine. However, they have been limited to a few mammalian species. Here we found that a set of four mammalian transcription factor genes used to generate iPSCs in mouse and humans can induce a partially reprogrammed pluripotent stem cell (PR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
74
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(76 citation statements)
references
References 87 publications
1
74
0
1
Order By: Relevance
“…iPSCs were first derived from mouse fibroblasts by overexpression of four reprogramming factors-Oct4, Sox2, Klf4, and c-Myc-and subsequently from human fibroblasts by overexpression of OCT4, SOX2, LIN28, and NANOG (Takahashi and Yamanaka, 2006;Yu et al, 2007) after retroviral transfection. Retroviral and lentiviral delivery of core reprogramming factors allowed the derivation of iPSCs from several other mammals, including rat (Liao et al, 2009), dog (Shimada et al, 2010), pig (Esteban et al, 2009), rhesus monkey (Liu et al, 2008), sheep (Bao et al, 2011), goat , horse (Nagy et al, 2011), cattle (Han et al, 2011), buffalo (Deng et al, 2012), and of iPS-like cells from nonmammalian vertebrates (Rossello et al, 2013). iPSCs derived from somatic tissue are particularly promising in farm animals in which true, germline-competent embryonic stem cells (ESCs) could not yet be derived (Kumar et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…iPSCs were first derived from mouse fibroblasts by overexpression of four reprogramming factors-Oct4, Sox2, Klf4, and c-Myc-and subsequently from human fibroblasts by overexpression of OCT4, SOX2, LIN28, and NANOG (Takahashi and Yamanaka, 2006;Yu et al, 2007) after retroviral transfection. Retroviral and lentiviral delivery of core reprogramming factors allowed the derivation of iPSCs from several other mammals, including rat (Liao et al, 2009), dog (Shimada et al, 2010), pig (Esteban et al, 2009), rhesus monkey (Liu et al, 2008), sheep (Bao et al, 2011), goat , horse (Nagy et al, 2011), cattle (Han et al, 2011), buffalo (Deng et al, 2012), and of iPS-like cells from nonmammalian vertebrates (Rossello et al, 2013). iPSCs derived from somatic tissue are particularly promising in farm animals in which true, germline-competent embryonic stem cells (ESCs) could not yet be derived (Kumar et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…We showed that Xenopus differentiated skeletal muscle fibers could be reprogrammed to pluripotency after transfecting the Yamanaka factors (mouse Oct4, Sox2 and Klf4). This was the first time that induced reprogramming was reported to be feasible in vivo and that mammalian factors were shown to be able to reprogram nonmammalian cells (Vivien et al 2012); others have confirmed these observations (Abad et al 2013;Rosselló et al 2013). This safe and inexpensive technique has been adapted to fish (Hansen et al 1991) including zebrafish (L. Coen, unpublished data), Xenopus tropicalis (Rowe et al 2002), and used in various species to develop immunization protocols (Donnelly et al 1995;Lewis and Babiuk 1999;Pachuk et al 2000).…”
Section: Discussionmentioning
confidence: 72%
“…A recent report has also demonstrated the development of ciPSCs capable of producing chimeric chickens (Rossello et al, 2013). These cells were developed using viral approaches, yet they still demonstrated limited incorporation in embryonic chicks, even when using low-passage cells.…”
Section: Discussionmentioning
confidence: 96%